2007
DOI: 10.1007/s10592-007-9284-4
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of new microsatellite markers for ginseng (Panax ginseng C. A. Meyer)

Abstract: Panax ginseng C.A. Meyer, commonly known as Korean or Asian ginseng, is a perennial herb native to Korea and China. Its roots are highly prized for several medicinal properties. The present study describes development and characterization of twentytwo polymorphic microsatellite markers for this species. A total of 99 alleles were detected with an average of 4.5 alleles per locus across 20 accessions. Values for observed (H O ) and expected (H E ) heterozygosities ranged from 0.05 to 1.00 and from 0.18 to 0.73,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 4 publications
(6 reference statements)
1
29
1
1
Order By: Relevance
“…Characterization of SSR-containing clones in the enriched library with reference to relative abundance of various repeat motifs revealed predominance of tri-nucleotide SSR (53.02%) over di-nucleotide SSR (37.21%). This is a feature common to other plant genomes, as several recent surveys on distribution patterns of various SSRs in genomic sequences of several plant species, including Arabidopsis (Morgante et al, 2002), foxtail millet (Jia et al, 2009), garlic (Ma et al, 2009), ginseng (Ma et al, 2007), Italian millet [our unpublished results], Medicago, Lotus, and Glycine (Mun et al, 2006), mung bean (Gwag et al, 2006), rice (Goff et al, 2005), and sesame (Dixit et al, 2005), have indicated that tri-nucleotide repeats are the most common type of SSR in plants. Occurrence of the AG/GA class of repeat motif among di-nucleotide repeats is consistent with reports from other plant species (Langercrantz et al, 1993;Morgante and Oliveiri, 1993;Powell et al, 1996, our unpublished results).…”
Section: Discussionmentioning
confidence: 87%
“…Characterization of SSR-containing clones in the enriched library with reference to relative abundance of various repeat motifs revealed predominance of tri-nucleotide SSR (53.02%) over di-nucleotide SSR (37.21%). This is a feature common to other plant genomes, as several recent surveys on distribution patterns of various SSRs in genomic sequences of several plant species, including Arabidopsis (Morgante et al, 2002), foxtail millet (Jia et al, 2009), garlic (Ma et al, 2009), ginseng (Ma et al, 2007), Italian millet [our unpublished results], Medicago, Lotus, and Glycine (Mun et al, 2006), mung bean (Gwag et al, 2006), rice (Goff et al, 2005), and sesame (Dixit et al, 2005), have indicated that tri-nucleotide repeats are the most common type of SSR in plants. Occurrence of the AG/GA class of repeat motif among di-nucleotide repeats is consistent with reports from other plant species (Langercrantz et al, 1993;Morgante and Oliveiri, 1993;Powell et al, 1996, our unpublished results).…”
Section: Discussionmentioning
confidence: 87%
“…하지만 현재까지 인삼의 SSR 마커 개발 연구는 시작 단계 에 있고 일부 국내 연구진을 중심으로 약 80여종이 SSR 마 커가 개발되었으며, 주로 국내·외 수집종과 지역 재배종에 대한 유전적 다양성 평가와 국내 육성 품종 판별에 국한된 연 구가 진행되어왔다 (Ma et al, 2007;Kim et al, 2007;Nguyen et al, 2010 3. 유전자형 분석 마커에 대한 number of allele (N A ), major allele frequency…”
Section: 따라서 국내·외에서 다양한 유전자원을 수집하고 이들 유 전자원을 식물학적 분류 외부 형태적 특성 및 유전unclassified
“…Besides, many researchers have tried to identify ginseng species and varieties using SSR markers Ma et al 2007;Nguyen et al 2010;Bang et al 2011aBang et al , 2011b. SSR markers are important for several types of research, including the assessment of genetic diversity, development of genetic maps, comparative genomics, marker-assisted selection, and other plant breeding fields.…”
Section: Introductionmentioning
confidence: 99%